TIM-3 and TIM-1 Could Regulate Decidual γδTCR Bright T Cells during Murine Pregnancy - Jasper Nörenberg; Matyas Meggyes; Pal Jakso; Eva Miko; Aliz Barakonyi (Journal of Immunology Research)
Pregnancy is an immunological enigma where paternal antigens are present at the fetomaternal interface. What regulates the local immunotolerance, which is necessary to prevent rejection of the conceptus, is still under strong investigation. Gamma/delta T cells are believed to play a role in the local regulation of this immunotolerance towards the semiallogenic fetus. Gamma/delta T cells from the uterus and spleen of pregnant and nonpregnant mice were analyzed by flow cytometry. We confirmed that the rate of γδT cells in the decidua increases during murine pregnancy and half of decidual γδT cells are CD4+. Furthermore, we found a unique association of CD4 or CD8 coreceptor expression with their γδTCR intensity, where in all investigated groups CD4- or CD8-positive γδT cells seemed principally to be γδTCRdim. In addition, compared to peripheral γδT lymphocytes, a greater proportion of decidual γδT cells expressed the cytotoxic marker CD107a and markers of Th1 or Th2 polarization (TIM-3, TIM-1), where decidual γδTCRbright cells were characterized by high TIM-3 and TIM-1 receptor expression. On the other hand, no difference in the expression of CD160, a receptor with dual function affecting cytotoxicity and T cell inhibition, was detected. Within lymphocytes expressing CD107a, TIM-1, or CD160, the rate of γδT cells was significantly higher in the decidua. According to our results, cytotoxic potential of decidual γδTCRbright cells could be regulated by TIM-3 ligation, while the TIM-1 receptor seems to be able to influence the Th1-Th2 balance at the fetomaternal interface. These mechanisms could play a part in the active maternal immunotolerance towards the fetus, allowing an efficient protection against pathogens during healthy murine pregnancy.